Pengaruh faktor kepemimpinan transformasional terhadap perilaku kerja inovatif melalui kesiapan untuk berubah sebagai mediator - Aditianto, Pramudio; Amir, Muhammad Taufiq (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The global Covid-19 pandemic requires the business enterprise to be ready to be up against massive changes due to the uncertain conditions. Change is a requisite as the business enterprise is currently recalculation of its business which has an impact on efficiency. This efficiency makes employees have to innovate in their work to be more effective and efficient. For this reason, transformational leaders are required to direct employees to change as well as to behave innovatively. This research uses the approach of quantitative with a survey method. The object of research is PT Lativi Mediakarya with the subject of all employees from the staff to manager level. Primary research data were collected through research questionnaires. The research sample was 140 people represented all Directorates and Divisions. The data were analyzed using Structural Equation Modeling with Partial Least Square approach. Transformational Leadership was found to have a positive effect on Readiness for Change, but does not have a significant effect on Innovative Work Behavior. Readiness for Change had a positive effect on Innovative Work Behavior. The Readiness for Change had a role as a mediator in the influence between Transformational Leadership and Innovative Work Behavior. Leaders in companies need to act agilely in the face of changing conditions with uncertainty, but still need to highlight aspects of individual considerations in their transformational character. Transformational leaders need to play a role in providing a stimulus for creativity and innovation so that they always encourage innovative behavior to their followers. Innovative behavior requires positive psychological conditions with trust and clarity of information from management.